2015
DOI: 10.4238/2015.may.22.2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of TG gene variants and their effects on growth, carcass composition, and meat quality traits in Chinese steers

Abstract: ABSTRACT. Thyroid hormones play an important role in regulating metabolism and can affect metabolism-related traits such as fat deposition. The thyroglobulin (TG) gene produces the precursor of thyroid hormones and has been proposed as a candidate gene for a quantitative trait locus with an effect on fat deposition. In this study, we identified 4 novel single nucleotide polymorphisms (SNPs) in the 5' flanking region of the TG gene using a DNA sequencing method. The SNP marker association analysis indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…This gene has been extensively studied in cattle and is known to be associated with the live weight and fat content of muscles (Zhang et al . ), marbling score (Casas et al . ), fat thickness and longissimus muscle area (Casas et al .…”
Section: Major Candidate Genes Associated With Pork Production Meat mentioning
confidence: 99%
“…This gene has been extensively studied in cattle and is known to be associated with the live weight and fat content of muscles (Zhang et al . ), marbling score (Casas et al . ), fat thickness and longissimus muscle area (Casas et al .…”
Section: Major Candidate Genes Associated With Pork Production Meat mentioning
confidence: 99%
“…It is known that the level of milk productivity is a polygenic trait controlled by various genetic loci (Dybus et al, 2004;Singh et al, 2014), some of which are already known (Singh et al, 2014;Khatami et al, 2005), and some are only classified as candidate genes (Viale et al, 2017). Based on literature data, the following economically valuable traits gene loci were selected for our work: kappa-casein (CSN3) (Chasovshchikova et al, 2017), beta-lactoglobulin (LGB) (Di Gregorio et al, 2017), prolactin (PRL) (Chasovshchikova et al, 2017), somatotropin (GH) (Akyuz et al, 2015;Metin Kiyici et al, 2019), thyroglobulin (TG5) (Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The DGAT1 gene genetic variants was primarily associated with milk production (Thaller et al, 2003), but several later studies reported the association between SNPs in DGAT1 gene and marbling and fat thickness (Wu et al, 2012;Tait et al, 2014). Like the DGAT1 gene, the genes encoding thyroglobulin and stearoyl-CoA desaturase are considered to be a perspective genetic marker for intramuscular fat levels as well as marbling scores in beef (Wu et al, 2012;Zhang et al, 2015;Bennett et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
“…It was shown that both flavour and tenderness scores markedly increased with increasing IMF content (Thomson, 2004). Previous studies have indicated that single nucleotide polymorphisms in the diacylglycerol-Oacyltransferase1 (DGAT1), thyroglobulin (TG) and Stearoyl-CoA desaturase (SCD) genes are significantly associated with intramuscular fat levels as well as marbling scores in beef (Pannier et al, 2010;Wu et al, 2012;Zhang et al, 2015). The objective of our study was to genotype the single nucleotide polymorphisms in six genes previously reported as candidate for beef quality in order to determine the genetic structure of Pinzgau bulls population.…”
Section: Introductionmentioning
confidence: 99%